The Role of E-Government Implementation, Transparency, Responsiveness, and Trust in Enhancing Citizen Satisfaction - Muhammad Nur; Herwantono; Yenniwati Sinaga; Samuel Indrayana (Journal Management & Economics Review (JUMPER), 2026)
The present research will focus on the importance of the implementation of e-government, transparency, responsiveness, and trust for enhancing citizen satisfaction. The fast development of information and communication technologies has prompted governmental agencies to implement electronic systems which should provide efficient and good-quality services to their citizens. Even though there is already much evidence about the extensive use of e-government systems, differences in the level of service provided can imply that some other governance factors such as transparency, responsiveness, and trust can affect the perception and evaluation of services provided to the public. This research will use a quantitative methodology and a cross-sectional survey design. The sample of 120 people was used for collecting data. All respondents have experience in using e-government systems and have answered a number of questions regarding their satisfaction with the process. Multiple linear regression was applied for data analysis, and it revealed that implementation of e-government, transparency, responsiveness, and trust positively affect citizen satisfaction. Among these variables, trust is the most influential one as it reflects the importance of citizen trust in government institutions. The developed model explains 61% of the variance in the level of citizen satisfaction.